Expectations Unfulfilled: Norwegian Migrants in Latin America, 1820-1940 - A. Sæther, Steinar (Studies in Global Migration History, 2016)
In Expectations Unfulfilled scholars from Argentina, Belgium, Brazil, Mexico, Norway, Spain and Sweden study the experiences of Norwegian migrants in Latin America between the Wars of Independence and World War II.